Assessment and analysis of lead, cadmium, zinc, copper in Aristeus antennatus shrimp’s from mediterranean coast of Algiers and evaluation of freshness by total volatile basic nitrogen test, before and after freezing - Chabha BENMOHAND; Lynda AÏNOUZ; Fatma Amira HANI; Mohamed ZAOUANI; Sofiane BOUDJELLABA; Madjid AKKOU; Amel MILLA; Djamel KHELEF (Revista Electronica de Veterinaria, 2024)
Seafood is the main source of exposure to environmental contaminants. However, risk-benefit analysis indicates that, in most of cases, the benefits associated to fish and seafood consumption outweigh the risks. The present study intended to determine the concentration of cadmium (Cd), lead (Pb), copper (Cu), zinc (Zn) and the Total Volatile Basic Nitrogen (TVB-N) level in Aristeus antennatus shrimp’s, from the Mediterranean coast of Algiers, before and after freezing. After Freeze-drying and samples mineralization, Cd, Pb, Cu, Zn concentrations were determined by Atomic Absorption Spectrometry method. TVB-N level determination was performed following the EC N. 2074 (2005) regulation method, at different conservation temperatures. The results showed that the concentrations of Cd, Pb, Zn and Cu respectively, were below the Detection Limit (BDL), 0.072, 0.091 and 0.019 mg/kg in unpeeled shrimps and 0.048, 0.072 and 0.011mg/kg in the peeled ones. All trace metal elements concentrations were statistically different; however, they were below the maximum recommended limits for human consumption set by WHO and FAO(2017). Furthermore, the TVB-N levels were 5.64 mg/100 g in fresh shrimps, 17.95 mg/100g in shrimps frozen at -18°C, 23.998 mg/100g in shrimps frozen at -18°C and then chilled at 4°C for 5 days, and 42.64 mg/100 g in shrimps chilled at 4°C for 5 days. Statistical analysis revealed a significant difference. We conclude that metal trace elements were within the acceptable range, and freezing ensures good preservation of the quality of the shrimps.